Effect of deposition thickness on microstructure and thermal behaviour of ZnO-Mg coated AISI 4140 for automotive applications. (August 2021) - Ramkumar, T; Selvakumar, M; Mohanraj, M; Senthilkumar, AP; Narayanasamy, P
In this research article, the detailed morphology characterization and thermal behaviour of AISI 4140 steel coated with ZnO-Mg were studied. Coating thickness of approximately ≈ 30, 60 and 90 µm were taken. The surface morphology of the coated samples was studied using Optical Microscope (OM) and Scanning Electron Microscope (SEM). Phases present in the coated samples were confirmed using X-Ray Diffraction Technique (XRD) and Raman Spectroscopy. Thermal properties of the coated samples such as thermal conductivity and thermal diffusivity were determined. In addition, specific heat of the coated samples was also identified. The samples with coating thickness of 30 µm exhibit enhanced thermal properties compared to other coated samples. The results reveal that ZnO-Mg coating can significantly improve the thermal properties of AISI 4140 steel, which can be a fair candidate material for automotive applications.